Analysis of Clean Water Demand and Water Availability at PDAM Water Treatment Plant (Case Study: Nagari Aur Kuning, Pasaman District, West Pasaman District) - Aidil Amri, Imam; Fajra, Melda; Marni, Elly (Greenation International Journal of Engineering Science, 2023)
Water is an absolute need for living things, especially humans. The availability of clean water must be evenly distributed by making the most of clean water sources. This study aims to determine the estimated population and plan the amount of water demand up to 2030 or the next 15 years . Analysis of projected population growth data and predictions of clean water needs in 2030 or the next 15 years is by using the geometric method. The results of this study indicate that the predicted population in 2030 or the next 15 years is 22,044 people and the prediction of water demand until 2030 or the next 15 years is 78.93 l/s.